2011
DOI: 10.1007/s10096-010-1144-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and differentiation of Trichophyton rubrum clinical isolates using PCR-RFLP and RAPD methods

Abstract: Trichophyton rubrum represents the most frequently isolated causative agent of superficial dermatophyte infections. Several genotyping methods have recently been introduced to improve the delineation between pathogenic fungi at both the species and the strain levels. The purpose of this study was to apply selected DNA fingerprinting methods to the identification and strain discrimination of T. rubrum clinical isolates. Fifty-seven isolates from as many tinea patients were subjected to species identification by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Polymerase chain reaction (PCR)-based techniques shorten the diagnostic procedure and generally have high sensitivity and specificity compared to conventional methods [53]. Many PCR-based techniques such as PCR fingerprinting [54,55], Random Amplification of Polymorphic DNA (RAPD) [56], Restriction Fragment Length Polymorphism (RFLP) [57] and real-time PCR [58]. Further, TRFLP (PCRterminal restriction fragment length polymorphism) [59], nested PCR [60] or PCR-ELISA [61] have also found there use in identification of previously cultured dermatophytes however, [62] used PCR-based methodology for dermatophytes from hair samples of cats.…”
Section: Molecular Identificationmentioning
confidence: 99%
“…Polymerase chain reaction (PCR)-based techniques shorten the diagnostic procedure and generally have high sensitivity and specificity compared to conventional methods [53]. Many PCR-based techniques such as PCR fingerprinting [54,55], Random Amplification of Polymorphic DNA (RAPD) [56], Restriction Fragment Length Polymorphism (RFLP) [57] and real-time PCR [58]. Further, TRFLP (PCRterminal restriction fragment length polymorphism) [59], nested PCR [60] or PCR-ELISA [61] have also found there use in identification of previously cultured dermatophytes however, [62] used PCR-based methodology for dermatophytes from hair samples of cats.…”
Section: Molecular Identificationmentioning
confidence: 99%
“…Analysis of ITS region based on RFLP-PCR was used to identify and discriminate between 57 T. rubrum clinical isolates (Hryncewicz-Gwóźdź et al, 2011) and between different species or varieties of Trichophyton, Microsporum and Epidermophyton (Gräser et al, 1999(Gräser et al, , 2000a(Gräser et al, and 2000bMirzahoseini et al, 2009). They reported that PCR-RFLP serves as a rapid and reliable method for the identification of T. rubrum isolates and other species of dermatophytes, while the RAPD analysis is rather a disadvantageous tool for T. rubrum strain typing while, De Baere et al (2010) reported that ITS2-RFLP analysis proved to be most useful for identification of species of the genera Arthroderma, Chrysosporium and Epidermophyton, but could not distinguish between several Trichophyton species.…”
Section: T Mentagrophytes (E)mentioning
confidence: 99%
“…When occurring in the toenails, onychomycosis is due more commonly to dermatophytes whereas in the fingernails the most common agents are yeasts . By far the most common causative agents of onychomycosis is Trichophyton rubrum and Trichophyton mentagrophytes that have been found to be the causative agent of onychomycosis in at least 90% of cases …”
Section: Introductionmentioning
confidence: 99%
“…7 By far the most common causative agents of onychomycosis is Trichophyton rubrum and Trichophyton mentagrophytes that have been found to be the causative agent of onychomycosis in at least 90% of cases. 2,9,10 The management of onychomycosis poses a difficult therapeutic challenge due to the slow growth of nails, the need for long-term application of topical and/or systemic medications. This in turn, translates into low cure rates and frequent relapses.…”
Section: Introductionmentioning
confidence: 99%